American primitive : poems - Oliver, Mary, 1935-2019. (Toronto : Little, Brown and Company, 1983)
50 lyrical poems by the author express renewal of humanity in love and oneness with the natural.
August -- Mushrooms -- The kitten -- Lightning -- In the pinewoods, crows and owl -- Moles -- The lost children -- The bobcat -- Fall song -- Egrets -- Clapp's pond -- Tasting the wild grapes -- John Chapman -- First snow -- Ghosts -- Cold poem -- A poem for the blue heron -- Flying -- Postcard from flamingo -- Vultures -- An old whorehouse -- Rain in Ohio -- Web -- University Hospital, Boston -- Skunk cabbage -- Spring -- Morning at great pond -- The snakes -- Blossom -- Something -- May -- White night -- The fish -- Honey at the table -- Crossing the swamp -- Humpbacks -- A meeting -- Little sister pond -- The roses -- Blackberries -- The sea -- Happiness -- Music -- Climbing the Chagrin River -- Tecumseh -- Bluefish -- The honey tree -- In blackwater woods -- The plum trees -- The gardens.
Winner of the 1984 Pulitzer prize for poetry
'An Atlantic Monthly Press book.'
Koleksi Sumbangan : Abdul Ghafar Ibrahim (AGI)
Keywords: American poetry -- 20th century